Simulação de um sistema de geração de ar comprimido - Gonçalves, Gustavo Quintal (Universidade Federal de São Carlos, 2021)
Compressed air is an utility with several applications in industry. Cleaning of equipments and environment, operating pneumatic machineries and robots, drying tanks and spray dying are some examples of common applications of compressed air in industry. It also can be part of the packaging production process, for example in the blister’s cavity formation, where the tablet ou capsule medicines are inserted and stored. Due it’s wide application range, the demand of a contaminant-free and moisture-free compressed air may vary depending on its final usage. In pharmaceutical industry, it is common the usage of oil-free compressors with dryers to guarantee a compressed air production with pharmaceutical standards. A compressed air generation system in an industrial scale can consume up to 30% of all energy consumption in a plant, meaning this process can be very costly. It is important to know the theoretical energy consumption from the air compression system and perform comparisions with the real consumption for a better analysis and process optimization. This monography presents an analysis of a air compression generation systeam of a pharmaceutical industry located in the State of São Paulo, Brazil, and aims to estimate theoretical energy comsumption of the equipments. An expressive part of all enery consumption of this plant comes from the compressed air generation system, which contains two compression units that operates continuously. Each compression unit is composed by oil-free screw compressors, chillers, water separator and a coupled dryer. The specific energy consumtion was evaluated by the influence of the temperature from the outlet streams from each compression stage and by the moisture content in the inlet stream. The simulation of the compression unit was performed in the iiSe simulator software, considering acceptable hipothesis and data from the real process. The results obtained by the simulation were acceptable comparing with the data given by the manufacturer. The limit for the operation conditions of the equipments were also considered. Variations on the ambient air resulted in a difference of 8.2% on the energy demand of the compression system between the lowest and the highest temperatures in the range. Variations on relative humidity of the ambient air resulted in relevant differences on the energy demand of the compression system only in the conditions of high moisture content. The difference was 2.6% between the conditions of 0% and 100% of relative humidity for the ambient air.
Simulation of a compressed air generation system
Keywords: Simulação de processos; Process simulation; Geração de ar comprimido; Compressed air generation; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA